2000
DOI: 10.2337/diabetes.49.11.1865
|View full text |Cite
|
Sign up to set email alerts
|

Repeated 2-deoxy-D-glucose-induced glucoprivation attenuates Fos expression and glucoregulatory responses during subsequent glucoprivation.

Abstract: A condition of reduced responsiveness to hypoglycemia, known as hypoglycemia-associated autonomic failure (HAAF), occurs in diabetic patients in the wake of a prior hypoglycemic episode. This condition suggests that hypoglycemia alters central glucose-sensing mechanisms. This experiment examined the effects of repeated 2-deoxy-D-glucose (2DG)-induced glucoprivation on subsequent 2DG-induced feeding and hyperglycemic responses in rats. Fos immunoreactivity (ir) in adrenal medulla and brain sites involved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
64
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 52 publications
(47 reference statements)
3
64
0
Order By: Relevance
“…Glucose sensing structures have also been reported in the caudal part of the NTS in the medulla [22], where K ATP channels have been pharmacologically identified [37]. Our data showed no significant effect of low glucose on NPY overflow in the dorsal medulla in both control rats and diabetic rats.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Glucose sensing structures have also been reported in the caudal part of the NTS in the medulla [22], where K ATP channels have been pharmacologically identified [37]. Our data showed no significant effect of low glucose on NPY overflow in the dorsal medulla in both control rats and diabetic rats.…”
Section: Discussionsupporting
confidence: 64%
“…However, the characteristics of these neurons remain largely unknown. Several candidate transmitters are implicated in central glucose sensing, including some amino acids, catecholamines and neuropeptide Y (NPY) [19,22].…”
mentioning
confidence: 99%
“…As recent antecedent hypoglycemia reduces autonomic (epinephrine) and symptomatic (which normally prompts behavioral defenses such as eating) responses to subsequent hypoglycemia (6,7), a vicious cycle of recurrent hypoglycemia is created where hypoglycemia leads to further impairment of counterregulatory responses, which in turn begets more hypoglycemia and so forth (4,8). Although several mechanisms have been proposed for the development of HAAF, including increased brain glucose transport (9 -11), changes in brain fuel metabolism (12)(13)(14), altered hypothalamic activity (15,16), and changes in brain glucose sensing and signaling (17,18), the exact mechanism underlying this phenomenon is unclear.…”
mentioning
confidence: 99%
“…This is supported by the studies from Borg et al (1995; that demonstrate the direct infusion of the neuroglucopenic agent 2-deoxyglucose (2DG) into the ventromedial nucleus of the hypothalamus (VMH) results in activation of a neuroendocrine counter-regulatory response; and glucose infusion into the VMH can reverse the counter-regulatory response to peripherally-induced neuroglucopenia. Peripheral administration of 2DG can result in increased c-fos immunoreactivity in brainstem catecholamine neurons (an index of neuronal activation) in brainstem catecholaminergic neurons (Ritter and Dinh, 1994;Sanders and Ritter, 2000). Insulin-induced hypoglycemia has been reported not to result in increased c-fos expression in these neurons (Baffi et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This provides further evidence, with another marker of neuronal responsivity, that insulin hypoglycemia and neuroglucopenia may represent different stimuli to the CNS. Sanders and Ritter (2000) have recently reported that both brainstem c-fos activation and counter-regulatory responses to subcutaneous 2DG were blunted in animals pretreated with 10 daily injections of 2DG. This time course would allow for adaptive changes such as gene and protein expression in nerve terminals, or perhaps altered efficiency of glucose uptake by the CNS, as has been reported by Doyle et al (1995).…”
Section: Discussionmentioning
confidence: 99%